De Brusselse jeugd: tussen diversiteit en kwetsbaarheid - Muriel Sacco; Wendy Smits; Bram Spruyt; Dimo Kavadias; Caroline d’Andrimont (Brussels Studies)
Presented in a thematic manner, the aim of this synopsis is to paint a picture of French- and Dutch-speaking Brussels youth between the ages of 12 and 25, based on a great diversity of data and academic research published since 2005. The institutional and linguistic complexity which characterises the situation in Brussels and the production of research makes this type of exercise absolutely necessary. This inventory of knowledge regarding youth in Brussels sheds light on their extraordinary diversity and their vulnerability, as well as on the work to be carried out in order to fill the gaps and improve the information available for the stakeholders in the field. This synopsis therefore also constitutes a proposed research agenda.